To Take the Stairs or Not to Take the Stairs? Employing the Reflective-Impulsive Model to Predict Spontaneous Physical Activity - Marcos Daou; Keith R. Lohse; Matthew W. Miller (MDPI AG, 2017)
The reflective-impulsive model (RIM) has been employed to explain various health behaviors. The present study used RIM to predict a spontaneous physical activity behavior. Specifically, 107 participants (75 females; Mage = 20.6 years, SD = 1.92 years) completed measures of (1) reflections about spontaneous physical activity, as indexed by self-report questionnaire; (2) impulse toward physical activity, as indexed by the manikin task; and (3) (state) self-control, as indexed by the Stroop task. The dependent variable was whether participants took the stairs or the elevator to the study laboratory. Results revealed reflections toward spontaneous physical activity positively predicted stair-taking. Further, a significant impulse toward physical activity × self-control interaction was observed. This interaction revealed that participants with high self-control who had a high impulse toward PA were more likely to take the stairs than their counterparts with a low impulse toward PA, whereas the opposite was the case for participants with low self-control. However, the impulse × self-control interaction was not significant when employing a self-report measure of trait self-control. Thus, RIM may be a good framework with which to consider spontaneous physical activity, but careful consideration must be given when examining variables within RIM (e.g., the boundary condition of self-control).